Transformation analysis of oral epithelial dysplasia to carcinoma in-situ and squamous cell carcinoma by p53 expression and gene mutations - Mei Syafriadi (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: It is known that oral squamous epithelial dysplasia (SED) and carcinoma in-situ (CIS) are precancerous lesion and it could transform to squamous cell carcinoma (SCC). We had reported p53-Protein Over-Expression and Gene Mutational of Oral CIS, such as basaloid, verrucous, and acanthothic/atrophic types, but demarcated between SED to CIS and CIS to SCC and how their transformation is still unclear. It is considered that their molecular behavior related one another. Purpose: To understand the molecular behavior of them we examined p53 exon 5-8 gene mutation and their protein expression in the sequential cases. Methods: Using 10 cases formalin–fixed paraffin sections that composed SED appearance, CIS and SCC in the same case were subjected to P53 immunohistochemistry. Then all cases were subjected to p53 gene mutations analysis. By laser capturing microdissection dysplasia part, CIS part and SCC part were cutted, and followed by direct sequencing of PCR product for exon 5-8. Result: SED p53-protein over-expression in some cells, and the expression was increased to CIS and SCC. Mutational analysis for p53 gene showed that 60% of p53 gene mutation in CIS also found in SCC, therefore SCC had additional mutation in other exon of p53 gene. While no particular mutations were found in SED part of all cases. Conclusion: Carcinoma in-situ is a squamous cell carcinoma eventhough not invasive yet, but squamous epithelial dysplasia is an early step to malignancy. It needs other genes examination to know any genes are involved in the precancerous to cancer transformation process.